What matters for internal migration, jobs or amenities? - Niedomysl, Thomas; Clark, William A V (Migration Letters, 2014)
There is an ongoing debate about whether jobs or amenities matter more for economic growth and by extension for regional migration. We review these debates briefly and point out that amenities are not always well defined and that the “either or” approach neglects the complexity of the migration process and the role that social processes play in the migration decision. While we acknowledge that there is still considerable ambiguity over the role that returns to employment play for internal migration decisions, this does not necessarily mean that the ambiguity can be replaced by calling on amenities as the major force in explaining migration flows.